Design Of Simulation Application System For Corporate Income Tax - Meilano, Rezagi; Saputra, Ferdyan Wana; Ayuningrum, Niken; Handoko, Dedi (Politeknik Negeri Madiun, 2024)
The design of the corporate income tax simulation application system aims to provide an effective and efficient tool for companies in calculating income tax liabilities in accordance with applicable tax regulations. The research method used is to start identifying problems through literature studies related to corporate taxes and interviews with users. Then analyze the needs related to the required features, security, performance and ease of use. The development system used is the waterfall model method. The waterfall model method is one of the software development models in the SDLC (Sequencial Development Life Cycle) model. Waterfall models are often also called linear sequence models or classic life flows. Key features developed include an intuitive user interface, flexibility in handling companies of various sizes, and strict data security to protect sensitive financial information. With a comprehensive design and focusing on user needs, this application is expected to be a reliable solution in supporting corporate income tax management.